Awareness and readiness to integrate AI with traditional library services - Suebat Ajoke Busari; Amina Alhassan Idris (Himpunan Pengembang Kurikulum Indonesia, 2026)
The rapid development of AI has created opportunities for academic libraries to enhance traditional library services. However, awareness of AI does not necessarily translate into readiness or actual utilization. This study aimed to examine library staff's awareness, readiness, and utilization of AI, potential areas for AI integration, and barriers to integrating AI with traditional library services in selected academic libraries in Kwara State. A quantitative descriptive survey design was employed using a structured questionnaire administered to randomly selected library staff. Of the questionnaires distributed, 120 were valid and analyzed using frequency counts and percentages. The findings indicate that library staff generally recognize the potential of AI, but their readiness to integrate it into traditional library services remains limited. AI was perceived as particularly suitable for information-oriented and user-support services, especially reference services, while its actual utilization remained relatively low. The findings further reveal that concerns about job displacement constitute the most prominent barrier, followed by shortages of AI expertise, unreliable power supply, inadequate infrastructure, and limited government support. The study concludes that effective AI integration requires continuous staff training, adequate technological infrastructure, institutional support, and policies that position AI as a complementary technology while preserving the professional and human-centered functions of library staff. Abstrak Perkembangan AI membuka peluang bagi perpustakaan akademik untuk meningkatkan layanan perpustakaan tradisional. Namun, kesadaran terhadap AI tidak selalu diikuti oleh kesiapan dan pemanfaatan yang nyata. Penelitian ini bertujuan untuk mengkaji kesadaran, kesiapan, pemanfaatan, potensi integrasi AI, serta hambatan integrasi AI dalam layanan perpustakaan tradisional di perpustakaan akademik terpilih di Kwara State. Penelitian ini menggunakan desain survei deskriptif kuantitatif dengan kuesioner terstruktur yang diberikan kepada staf perpustakaan yang dipilih secara acak. Sebanyak 120 kuesioner valid diukur menggunakan frekuensi dan persentase. Hasil penelitian secara umum menunjukkan bahwa staf perpustakaan telah mengenal potensi AI, tetapi kesiapan untuk mengintegrasikannya ke dalam layanan perpustakaan tradisional masih terbatas. AI dipandang paling sesuai untuk layanan yang berorientasi pada informasi dan dukungan pengguna, khususnya layanan referensi, sementara pemanfaatannya dalam praktik masih relatif rendah. Kekhawatiran akan kehilangan pekerjaan menjadi hambatan utama, diikuti oleh kekurangan tenaga ahli AI, pasokan listrik yang tidak andal, keterbatasan infrastruktur, serta kurangnya dukungan pemerintah. Kesimpulan penelitian menunjukkan bahwa integrasi AI memerlukan pelatihan berkelanjutan, infrastruktur teknologi yang memadai, dukungan institusional, serta kebijakan yang menempatkan AI sebagai pelengkap teknologi dengan tetap mempertahankan fungsi profesional dan humanis staf perpustakaan. Kata Kunci: integrasi AI; pelatihan berkelanjutan; penerapan teknologi; perpustakaan akademik